IMPROVING QUALITY OF LIFE WITH NON-PHARMACOLOGICAL APPROACH FOR ADULT WITH HEMOPHILIA: A SYSTEMATIC REVIEW - Adha, Alfi Kurnia; Sri Yona; Riri Maria (Universitas Kadiri, 2025)
Factor VIII/IX deficiency in hemophilia make patients susceptible to joint bleeding (hemarthrosis), especially in the knee, elbow and ankle joint. Repeated bleeding episodes trigger chronic joint damage (arthropathy) and pain, thus disrupting functional status, limiting social life which ultimately reduces quality of life. In Indonesia, factor VIII/IX replacement concentrate is the main treatment for hemophilia which is given on-demand. Its is because the price is still relativelt expensive and the stock is unevenly distributed in all regions. This systematic review aims to explore various non-pharmacological approaches that are eddective in improving the quality of life of adult with hemophilia. The method used in this research is article searches. Data obtained from 8 databases such as PubMed, ScienceDirect, Scopus, Wiley, ClinicalKey Nursing, Taylor & Francis, Proquest and Springer Nature Link by filtering articles based on year of publication, title, abstract and full text. The result obtained 10 articles that match with inclusion and exclusion criteria. There were three aspects of quality of life in hemophilia, five articles focused on addressing problems in the physiological aspect, five anothers discussed problems in the psychological aspect, and only one study intervened social aspect. Intervensions were carried out with various method such as education, watching virtual reality videos, counseling, hypnosis, use of knee support and physical exercise. Non-pharmacological approaches have been shown to improve quality of life with various intervention, but all interventions were given when there was no acute bleeding episodes (hemarthrosis).